MENGANALISA SIKAP SEBAGAI UPAYA UNTUK MENGIDENTIFIKASI KEBERHASILAN MAHASISWA IPDN - aam alamsyah (Institut Pemerintahan Dalam Negeri, 2019)
This article highlights attitudinal analysis which can be used to predict the students’ accomplishment in their study. Analyzing the learners’ attitudes can possibly improve the validity of evaluation which is generally conducted by both lecturers and administrators either during the recruitment or in the teaching/learning process. Besides, this attempt can also be used to predict the students’ potential accomplishment when learning in IPDN. Attitude, which is commonly defined as a behavioral tendency to act in certain patterns, is very important to be analyzed in order to allow the lecturers to have more objective description of the students’ behavior and their potential accomplishment. If this thoroughly applied, attitudinal analysis will not only allow the lecturers and other related staffs to evaluate the good quality candidates, but also allow them to assess the students’ potential success. In line with the continuously increasing demand of the society toward the officials who have more integrity, analyzing attitudes can help select those having good quality, more integrity, and being more prepared in serving the society.